Two new names in Clematis (Ranunculaceae) - Falck, Daniel; Lehtonen, Samuli (Phytotaxa, 2014)
Molecular studies (Miikeda et al. 2006, Xie et al. 2011) have established that the genus Naravelia Adanson (1763: 460) nom. cons. is nested within the genus Clematis Linnaeus (1753: 543). Most of the names treated under Naravelia have combinations in Clematis already. However, N. siamensis Craib and N. pauciflora H.Eichler have not been transferred to Clematis, apparently because of the existing homonyms. Here, we provide new names for them.